Pengamalan al-Ṭarīqah al-Ṣūfiyyah Sebagai Motivasi Spiritual Bagi Penagihan Dadah: The Practice of al-Ṭarīqah al-Ṣūfiyyah as a Spiritual Motivation for Drug Addiction - Ibrahim, Nursyahidah; Syed Abdul Rahman, Syed Mohammad Hilmi; Mohd Azhar, Muhammad Hazim (Jurnal Usuluddin, 2021)
The statistics of drug abuse in the country is always at worrying levels. Various methods have been employed by the government and other parties in preventing and treating this problem. Among of the treatment for drug addiction is through the approach of sufism by implementing the practice in al-Ṭarīqah al-Ṣūfiyyah through the emphasis on the needs and the methods of spiritual motivation. By applying the interview method and descriptive analysis, this study was conducted at Pondok Remaja Inabah Kuala Nerang to obtain informations on drug addiction treatment methods via the practice of Ṭarīqah Qadiriyah wa Naqshabandiyyah. Managers or practitioners as well as four trainees were interviewed to obtain more detailed regarding the information on the methods and also on the experiences of the trainees which is has been exposed to this method of spiritual motivation. This study found that the spiritual aspect using the methodology of al-Ṭarīqah al-Ṣūfiyyah taken by practitioners of Ṭarīqah Qādiriyah wa Naqshabandiyyah is able to be an alternative or complementary treatment to existing drug addiction rehabilitation treatment in addition to developing human personality. Mandi taubat, solat and zikir are the three main motivational stimulant practices in the treatment of drug addiction.